Analisis Penerapan Sistem Informasi Akuntansi Pada Akuntabilitas Pengelolaan Alokasi Dana Desa (ADD) Di Desa Tanjung Selamat Kec. Percut Sei Tuan - Morina Sari Simamora; Nurlaila Nurlaila; Nurul Inayah (Sekolah Tinggi Ilmu Ekonomi Trianandra, 2023)
The aim of this research is to find out how accounting recording techniques are used in Tanjung Selamat Village, Kec. Percut Sei Tuan, and how it impacts the accountability of village allocation control (ADD). Qualitative descriptive is a type of research methodology used in this research. using data collection techniques, document analysis, and interviews. To speak for the village secretary and treasurer and collect documents related to budget realization records, this research uses a data collection strategy. Based on research findings, Tanjung Selamat Village in Kec. Percut Sei Tuan has created an accounting record system as a consequence of using village financial techniques (siskeudes). The application of accounting record techniques to the general control of accountability for village capital allocation proves that the implementation of village equity allocation is transparent, accountable and accountable. There are only a few obstacles, such as submitting the budget to the village head, which sometimes causes delays. But overall the practice of village financial control is very good and in line with PERMENDAGRI number 20 of 2018.